MODEL QUANTUM LEARNING BERBASIS NEAR POD UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISTEM PENCERNAAN SISWA DIGITAL NATIVE ERA SOCIETY 5.0 - Anjarwati, Ani; Siti Qomariyah, Ryzca; Fatimattus Az Zahra, Putri (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
As an educators, it is important to apply the learning principles of motivation, attention, activity, and feedback to ensure successful learning. However, in reality there are various obstacles that prevent students from achieving high learning outcomes. This happens to class VD students at Gloria 3 Christian Elementary School, Surabaya, where they often experience learning difficulties, especially in the subject